Paired Expression Analysis of Tumor Cell Surface Antigens - Orentas, Rimas J.; Sindiri, Sivasish; Duris, Christine; Wen, Xinyu; He, Jianbin; Wei, Jun S.; Jarzembowski, Jason; Khan, Javed (Frontiers in Oncology, 2017)
Adoptive immunotherapy with antibody-based therapy or with T cells transduced to express chimeric antigen receptors (CARs) is useful to the extent that the cell surface membrane protein being targeted is not expressed on normal tissues. The most successful CAR-based (anti-CD19) or antibody-based therapy (anti-CD20) in hematologic malignancies has the side effect of eliminating the normal B cell compartment. Targeting solid tumors may not provide a similar expendable marker. Beyond antibody to Her2/NEU and EGFR, very few antibody-based and no CAR-based therapies have seen broad clinical application for solid tumors. To expand the way in which the surfaceome of solid tumors can be analyzed, we created an algorithm that defines the pair-wise relative over-expression of surface antigens. This enables the development of specific immunotherapies that require the expression of two discrete antigens on the surface of the tumor target. This dyad analysis was facilitated by employing the Hotelling’s T-squared test (Hotelling-Lawley multivariate analysis of variance) for two independent variables in comparison to a third constant entity (i.e. gene expression levels in normal tissues). We also present a unique consensus scoring mechanism for identifying transcripts that encode cell surface proteins. The unique application of our bioinformatics processing pipeline and statistical tools allowed us to compare the expression of two membrane protein targets as a pair, and to propose a new strategy based on implementing immunotherapies that require both antigens to be expressed on the tumor cell surface to trigger therapeutic effector mechanisms. Specifically, we found that for MYCN amplified neuroblastoma, pairwise expression of ACVR2B or ALK with GFRA3, GFRA2, CDH24 or with one another provided the strongest hits. For MYCN non-amplified stage 4 neuroblastoma, NTRK1 or ALK paired with GFRA2, GFRA3, SSK1, GPR173 or with one another provided the most promising paired-hits. We propose that targeting these markers together would increase the specificity and thereby the safety of CAR-based therapy for neuroblastoma.